Programming languages for data-Intensive HPC applications: A systematic mapping study - Amaral, Vasco (2020)
This work is a result of activities from COST Action 10406 High -Performance Modelling and Simulation for Big Data Applications (cHiPSet), funded by the European Cooperation in Science and Technology. FCT, Portugal for grants: NOVA LINCS Research Laboratory Ref. UID/ CEC/ 04516/ 2019); INESC-ID Ref. UID/CEC/50021/2019; BioISI Ref. UID/MULTI/04046/2103; LASIGE Research Unit Ref. UID/CEC/00408/ 2019.